Private School Physical Education Online Learning Implementation During Pandemic of Covid in Karanganyar Regency - Avin Giovanus; Sunardi Sunardi; Waluyo Waluyo (PHEDHERAL, 2022)
The purpose of this study was to determine the application of PJOK online learning in private schools in Karanganyar District. This research is a description of the process of implementing learning during the Covid-19 pandemic. This research is a qualitative research. Qualitative research using data collection techniques with survey methods. The subjects of this study were teachers of PJOK of private junior high schools in Karanganyar District, Karanganyar Regency, totaling 9 people. Data collection techniques are by observation, interviews, and documentation. The results of the study show that all teachers strongly support government policies to carry out online learning during the Covid-19 pandemic in a responsible way to carry out their duties properly. Constraints that often occur in the implementation of online learning are internet networks, quotas and communication tools used by students to carry out learning. To overcome this, each school provides print outs of assignments and material package books that can be taken for students who are constrained in participating in online learning. The teacher plans learning according to the latest RPP, then carries out learning using the WhatsApp and Ukline applications. The impact of this application makes all teachers carry out PJOK learning which is entirely carried out using online media.